2022
DOI: 10.1021/acs.macromol.2c00460
|View full text |Cite
|
Sign up to set email alerts
|

Chain Entanglements and Interlamellar Links in Isotactic Polybutene-1: The Effect of Condis Crystals and Crystallization Temperature

Abstract: Chain entanglements, which reside in the amorphous phase of semicrystalline polymers, influence many macroscopic properties of polymers. There are different opinions about the role of crystallization and subsequent melting in the entanglement density. Isotactic polybutene-1 (iPB-1) was selected for this study. Crystallization of this polymer from an equilibrated melt led to the formation of conformationally disordered (condis) form II crystals with high chain mobility enabling long-range chain diffusion, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…39,40 In Form I crystals, the crystalline 3/1 helices are almost completely immobile, prohibiting any overall and side-chain motion up to nominal melting point. 71,72 Thus, once a Form I crystal was nucleated within Form II lamellae, the mobility of the corresponding crystalline stems was slowed down drastically. Moreover, by virtue of the larger reduction in conformational entropy when changing a random polymer coil into 3/1 helices rather than 11/3 helices, 73 it is more difficult to straightforwardly produce Form I crystals from the isotropic amorphous melt.…”
Section: Resultsmentioning
confidence: 99%
“…39,40 In Form I crystals, the crystalline 3/1 helices are almost completely immobile, prohibiting any overall and side-chain motion up to nominal melting point. 71,72 Thus, once a Form I crystal was nucleated within Form II lamellae, the mobility of the corresponding crystalline stems was slowed down drastically. Moreover, by virtue of the larger reduction in conformational entropy when changing a random polymer coil into 3/1 helices rather than 11/3 helices, 73 it is more difficult to straightforwardly produce Form I crystals from the isotropic amorphous melt.…”
Section: Resultsmentioning
confidence: 99%
“…Dimensions of the lamellar structure for iPB-1 and iPB-1/C2 with form I were determined using a combination of SAXS and DSC data as described previously. , The calculation was also based on the analysis of the interface distribution function K″(z) . Figure a depicts the 1D SAXS intensity distribution profiles for iPB-1/C2 with form I.…”
Section: Resultsmentioning
confidence: 99%
“…Some dense locations of entanglements become the amorphous parts connecting the different crystals. 32,57 In the blended system with a long-chain content of 10% (C400), it can be clearly observed that the disappearance of entanglements and polymer crystallization are two simultaneous processes. During stretching, the locations where the disentanglement occurs first are more prone to crystallization.…”
Section: Mechanisms Of the "Catalyticmentioning
confidence: 99%